Journal Geon Vol 3 No 1 January June 2016 (GEON Journal (Management, Organizations and Business), 2016)
In this issue we present a reflection on Corporate Social Responsibility, then in Accounting and Finance, mention is made of the responsibility of the auditor in financial information fraud, a diagnosis to apply forensic auditing, the financing of microenterprises in Puebla, Mexico, and the role of the public accountant in the formulation of public policies. In marketing we talk about the communication of the brand and the contribution of market research and its use in decision-making and it ends with a performance evaluation article in the Vilavicencio clinics.
Keywords: Corporate Social Responsability; Auditor; Forensic Audit; public policy; accounting processes; financing in microentreprise; brand communication; market research; Marketing; Humana Management; Performance Evaluation